Penalaran Kuantitatif Siswa SMA dalam Menyelesaikan Soal HOTS - Guntur Aprilaksono (Program Studi Pendidikan Matematika STKIP PGRI Sidoarjo, 2020)
This study aimed to describe quantitative reasoning of high school students in solving HOTS questions. This research was conducted in SMA Muhammadiyah 3 Tulangan Academic Year 2019/2020. The subjects of this study were 3 students from Class X MIPA 2 which consisted of 1 student with high mathematical ability, 1 student with moderate mathematical ability, and 1 student with low mathematical ability. The instruments in this study which used qualitative approach were test and interview questions. The data obtained were then analyzed using time triangulation by comparing the first time data with the second time. The results showed among three students who have difference mathematical ability, there is only student that has high mathematical ability could apply various techniques to solve the problems (for the example, drew picture, used pattern, solved problem) and only student that has moderate mathematical ability could determine the limit of the problems.